2022
DOI: 10.1038/s41598-022-14754-1
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing and spinning of amorphous Lennard-Jones nanoparticles under oblique collisions

Abstract: Collisions of Lennard-Jones nanoparticles (NPs) may be used to study the generic collision behavior of NPs. We study the collision dynamics of amorphous NPs for oblique collisions using molecular dynamics simulation as a function of collision velocity and impact parameter. In order to allow for NP bouncing, the attraction between atoms originating from differing NPs is reduced. For near-central collisions, a finite region of velocities – a ‘bouncing window’ – exists where the 2 NPs bounce from each other. At s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
1
3
1
Order By: Relevance
“…Only central collisions were considered. We found that for all velocities in the range of 150–100,000 m/s, collisions between CO NPs were always sticking; this finding is in agreement with earlier simulations on amorphous LJ NPs 52 and our previous results on water-ice NPs 28 . We therefore present here only the results of a central collision with a relative velocity of LJ units; this corresponds to velocities of 276 (298, 424, 742) m/s for Ar (CO, CO , H O) according to Table 2 .…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Only central collisions were considered. We found that for all velocities in the range of 150–100,000 m/s, collisions between CO NPs were always sticking; this finding is in agreement with earlier simulations on amorphous LJ NPs 52 and our previous results on water-ice NPs 28 . We therefore present here only the results of a central collision with a relative velocity of LJ units; this corresponds to velocities of 276 (298, 424, 742) m/s for Ar (CO, CO , H O) according to Table 2 .…”
Section: Methodssupporting
confidence: 93%
“… Finally, our present study focused on central collisions, while in experiment and in nature large impact parameters will occur. Large impact parameters decrease the tendency for sticking as only parts of the colliding NPs come into close contact and experience their mutual attraction 52 , 59 . Recently, it was shown that energy dissipation in granular aggregates of water ice leads to different aggregation and fragmentation outcomes 60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a behavior has not been observed in the present study nor, to our knowledge, in other studies of aggregate collisions, except for unrealistically large filling factors (Wada et al 2011) or in aggregates composed of grains of very different masses such as dust-covered chondrules (Umstätter et al 2019). We note, however, that such a bouncing behavior is well-known for solid or liquid clusters (Kalweit & Drikakis 2006;Sommerfeld & Kuschel 2016;Nietiadi & Urbassek 2022).…”
Section: Collision Outcomescontrasting
confidence: 54%
“…We note that collisions of liquid droplets -of interest in technological applications such as spraying -have been classified similarly; however, the fragmentation regime is denoted as "stretching separation," where a multitude of small droplets are produced after the colliding droplets separate again (Ashgriz & Poo 1990;Estrade et al 1999;Sommerfeld & Kuschel 2016). Also collisions of solid clusters, analyzed with the help of molecular dynamics simulations, lead to a similar classification (Kalweit & Drikakis 2006;Nietiadi & Urbassek 2022).…”
Section: Collision Outcomesmentioning
confidence: 98%